2003
DOI: 10.1002/pros.10209
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray analysis reveals prognostic significance of syndecan‐1 expression in prostate cancer

Abstract: The results of this TMA study confirm a dominant prognostic significance of Gleason grading and Ki67 LI in prostate cancer, as compared to a less pronounced role of Bcl-2, and p53. We identified syndecan-1 as a new prognostic factor and provide evidence for an androgen-dependent regulation of CD-10 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
3
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 43 publications
12
133
3
8
Order By: Relevance
“…Few studies that have analyzed prediction of PCa-specific death, 39,46 -51 and even fewer have attempted to identify biomarkers of PCa-specific death. [52][53][54][55] The study reported here was possible because of our unique resources, including a large tissue bank and database with extensive follow-up clinical data for Ͼ15 years. Unlike most other cancers, PCa-specific death continues up to the 20th year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies that have analyzed prediction of PCa-specific death, 39,46 -51 and even fewer have attempted to identify biomarkers of PCa-specific death. [52][53][54][55] The study reported here was possible because of our unique resources, including a large tissue bank and database with extensive follow-up clinical data for Ͼ15 years. Unlike most other cancers, PCa-specific death continues up to the 20th year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated syndecans in prostate cancer, but were mostly focused on SDC1, [18][19][20][21] and only one addressed expression of SDC2. 16 Contreras et al 16 found SDC2 to be expressed in normal prostate tissue, BPH, PIN, and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a scanning system similar to that used in earlier studies of syndecan-1 (SDC1) expression in prostate cancer, in which at least moderate staining intensity was required in 410% of tumour cells to define SDC2 overexpression. 18,19 All samples were examined independently by three observers (AD, BK, and DT), and any difference was resolved by a joint review.…”
Section: Methodsmentioning
confidence: 99%
“…Localisation patterns were defined as membranous or cytoplasmic according to previous reports. [8][9][10]15 Intensity was scored as weak (1/111), moderate (11/111) or strong (111/111). The proportion of positive cells was evaluated as negative, ,40%, 40-80% or .80%.…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%
“…8 In addition, the overexpression of syndecan-1 was associated with a high Gleason score and a poor clinical outcome. 9 Recently, Shariat et al 10 showed that the expression of syndecan-1 was directly correlated with the Gleason score and associated with a high risk of PSA progression after 1 surgery. Nevertheless, the mechanisms involved remain largely unclear, and these differing results need to be addressed.…”
Section: Introductionmentioning
confidence: 99%